2014
DOI: 10.1038/npp.2014.127
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Non-Genetic Inheritance and Psychiatric Disorders

Abstract: Inheritance is typically associated with the Mendelian transmission of information from parents to offspring by alleles (DNA sequence). However, empirical data clearly suggest that traits can be acquired from ancestors by mechanisms that do not involve genetic alleles, referred to as non-genetic inheritance. Information that is non-genetically transmitted across generations includes parental experience and exposure to certain environments, but also parental mutations and polymorphisms, because they can change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 133 publications
(153 reference statements)
0
39
0
4
Order By: Relevance
“…Maternal effects on fetal development have been explored in other mouse models related to autism, but these studies have focused on environmental stressors that impact the prenatal environment (Bronson and Bale, 2014;Malkova et al, 2012). Recent studies related to mood and anxiety have indicated that genetic factors may also influence neurodevelopment by altering maternal physiology during pregnancy (Toth, 2014). Interestingly, maternal genotype effects on fetal development have been reported in offspring of 5-HT 1A and TPH1 null mice (Cote et al, 2007;Gleason et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal effects on fetal development have been explored in other mouse models related to autism, but these studies have focused on environmental stressors that impact the prenatal environment (Bronson and Bale, 2014;Malkova et al, 2012). Recent studies related to mood and anxiety have indicated that genetic factors may also influence neurodevelopment by altering maternal physiology during pregnancy (Toth, 2014). Interestingly, maternal genotype effects on fetal development have been reported in offspring of 5-HT 1A and TPH1 null mice (Cote et al, 2007;Gleason et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, perturbations such as parental stress, malnutrition, infection, or advanced age have been associated with an increased incidence of neurodevelopmental disease in offspring (1), and alterations in their hypothalamic-pituitary-adrenal (HPA) stress axis response may be central to increased disease predisposition (2,3). Studies in diverse animal models have demonstrated similar outcomes, particularly that of offspring HPA axis dysregulation, following either maternal or paternal stress exposure (4-7); yet mechanisms by which parental lifetime stress experience modify offspring development and adult phenotypes remain unclear.…”
mentioning
confidence: 99%
“…Toth (2015) reviews recent, intriguing research on intergenerational, non-genetic transmission of epigenetic information that alters brain development and impacts risk for mental illness. He presents the current evidence for the impact of the prenatal environment on such transmission, delineates the limitations of this work, and maps out the potential for future studies in animal models and in humans.…”
mentioning
confidence: 99%